Myanmar Agricultural Development Bank : Initial Assessment and Restructuring Options - World Bank (Bangkok, 2014)
Myanmar is an agricultural country. It is estimated that the agriculture sector represents between 35 to 40 percent of gross domestic product (GDP) and that up to 70 percent of the labor force (of 32.5 million) is directly or indirectly engaged in agricultural activities or depend on agriculture for their income. Given agriculture's important contribution to the economy, the modernization of the agriculture sector is a top priority in the economic and social development agenda of the Government of Myanmar. Among the government institutions supporting the agriculture sector, the Myanmar Agriculture Development Bank (MADB) plays an important role. MADB was established in June 1953 by the Government of Myanmar to support the development of agriculture, livestock, and rural enterprises in Myanmar. MADB is currently the largest financial institution serving the rural areas and financing agriculture activities. At the end of 2012, MADB served 1.87 million customers, mostly farmers, and had a network of 206 branches (which accounted for 23 percent of all banks' branches in Myanmar). Since its creation, MADB has played an important economic and social role by providing loans to a large segment of low-income households engaged in agricultural activities. Historically, several agriculture banks around the world have failed due to poor corporate governance, inadequate risk management capability, unsustainable business models, capture by their own clientele, or undue political interference in their lending decisions. Therefore, authorities should ensure that MADB is transformed into a sound, well-administered, and financially sustainable institution, able to withstand undue political interference and able to operate with the highest standards of corporate governance and transparency. In this context, the report is organized as follows: chapter one gives diagnostic of MADB; chapter two presents options for the transformation of MADB; chapter three presents lessons from international experience; and chapter four gives conclusions.